What’s flashing in Kadamaian? A note on Fireflies (Coleoptera: Lampyridae) in Kadamaian, Sabah - Vickly Mobilim; Mahadimenakbar Mohamed Dawood (Universiti Malaysia Sabah, 2021)
A firefly survey was conducted in Podos, Melangkap Noriou and Pinolobu in Kadamaian, Kota Belud during the Borneo Geographic Expedition Kadamaian 2019. A total of 48 fireflies were collected representing at least seven species consisting mainly of Luciola spp. and a single individual of Pyrocoelia sp. larva. Identification reveals that two samples are potentially new records to Borneo; cf. Aquilonia sp. and Medeopteryx sp., and also Luciola niah as a new record for Sabah. Furthermore, four samples have unique morphological characters including the potential Aquilonia and Medeopteryx samples and two Luciola samples. Fireflies were caught in various locations such as near rubber plantations, trails and rivers. Findings from this report expands the distributional knowledge about Lampyridae in Borneo.